Fiscal-financial vulnerabilities - Ludger Schuknecht (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
The paper analyses the linkages from financial developments to public finances. It maps and discusses the transmission channels to fiscal variables. These channels include asset prices, financing conditions, balance sheets of banks, non-banks and central banks and international linkages. The study argues that the fiscal effects via each and all these channels can be very serious in magnitude and can put the sustainability of public finances at risk. However, there is an only limited in-depth analysis of these channels and risks.
urn:nbn:de:hebis:30:3-509241
Keywords: 330